The Socialization of Android as Online Learning Media: A Systematic Review - Nurmala Hendrawaty; Muli Yani; Dian Suherman; Casmiati Casmiati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
The COVID-19 pandemic has changed the learning process from face-to-face to online. The socialization of Android as online learning media has been increasing during the pandemic. The implementation of educational technology makes Android an innovative and effective online learning media so that teachers and students can access it anywhere and anytime. Therefore, the research aims to socialize the use of Android phones as online learning media. The selections of works of literature are from several databases, including Garuda, Science Direct, Google Scholar, Research Gate, Web of Science, and Crossref. There are 30 articles selected and reviewed through a systematic review used as the research methodology. The journals were analyzed using a content analysis method; the diagrams and tables presented the data. The findings reveal that the Android application is user-friendly, innovative, and adaptive to the teaching and learning process; however, it faces challenges because a few students need help with the unstable signal, internet data and unsupported mobile phones. Nevertheless, Android is an applicable and effective online learning media for teachers and students.